Intensive Litopenaeus vanamei pond performance with irrigation system based on Distribution of Vibrio spp. - Claritha Madonsa; Bambang Widigdo; Majariana Krisanti; Munti Yuhana (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Intensive shrimp ponds are characterized by the high stocking density of shrimp and artificial feeding and are equipped with an irrigation network system. The purpose of this study was to analyze the intensive L.vannamei pond with an irrigation system based on Vibrio spp. distribution to determine environmental quality degradation in terms of the treat of pathogenic bacteria. This study was carried out for one production cycle from March toJuly 2021 in an intensive shrimp farm in Sarjo Village, Pasangkayu Regency, West Sulawesi. The parameters analyzed in this study consisted of Total Bacterial Count (TBC), Total Vibrio Count (TVC), yellow and green colony Vibrio spp. in water using the spread plate method. Water samples for bacterial analysis were taken from 1) source water: (a) surface (050 cm depth) and (b) pump mouth; 2) treatment pond; 3) aquaculture pond; 4) Waste Water Treatment Ponds (WWTP); 5) outlet (before discharge into public waters). The results showed that the distribution of bacteria from seawater to WWTPs pond still increased the abundance of Vibrio spp., although the abundance of Vibrio spp. is still safe or below the maximum limit of 104 CFU/mL. Distribution of Vibrio bacteria in Intensive L.vannamei Pond Sarjo Village, West Sulawesi gave a relatively good pond performance because it was characterized by an abundance of Vibrio bacteria in the pond irrigation system from inlet to outlet which was still below the maximum limit and high pond productivity.Keywords:Intensive shrimp pondPathogenicVibrio spp.Pond performanceAquaculture